Effect of microwave sintering on the densification and properties of copper oxide doped Y-TZP ceramics / Sara Lee Kit Yee - Sara Lee , Kit Yee (2019)
Yttria-tetragonal zirconia polycrystal (Y-TZP) exhibited good physical and mechanical properties which are advantageous in various engineering and dental applications. In the present work, the effect of microwave sintering on the properties of copper oxide (CuO) doped 3 mol% Y-TZP was studied. The results showed that the pre sintered green samples flanked with two susceptors in an enclosed alumina fiberboard housing subjected to microwave sintering (heating rate of 30 °C/min with a holding time of 5 min) had successfully produced crack-free sintered samples. Various amount of CuO ranging from 0.05 wt% to 1 wt % was incorporated in Y-TZP to study the effect of microwave sintering on phase analysis, microstructure, density, Vickers hardness and fracture toughness at different sintering temperatures (between 1100 °C and 1400 °C). It was found that the addition of up to 0.5 wt% CuO was beneficial in aiding densification of zirconia without inducing grain coarsening. In particular, 0.2 wt % CuO-doped Y-TZP achieved relative density ≥ 99%, Vickers hardness of 14.4 GPa, fracture toughness of 7.8 MPa.m1/2 and exhibited fine equiaxed tetragonal grain size of less than 0.25 μm when microwave sintered between 1250°C and 1300 °C. In contrast, the addition of 1 wt% CuO was detrimental and resulted in the formation of about 50% monoclinic phase upon sintering. This research also showed that the microwave effect was significant to enhance densification at low temperatures (< 1300 °C) for undoped Y-TZPs. On the other hand, the addition of 0.2 wt% CuO-doped Y-TZPs was found to be effective as a sintering aid for conventional sintering at temperatures ≥ 1200 °C as the resulting samples exhibited similar properties when using microwave sintering. Grain size was found to have played a role in suppressing the hydrothermal ageing of Y-TZP. It was found that all the samples with grain size of below 0.28 μm did not undergo the ageing induced phase transformation after 180 °C/10 bar for 200 h.